Influencia del deficiente clima laboral en el rendimiento de los trabajadores de la municipalidad distrital de laredo, en el año 2012. - Vásquez Horna, Ruth Karina (2013)
In the present research report there develops the study relating to the personalized individualized work and the crisis of institutional identity of the workers of the municipality distrital of Laredo, for what they are the social factors that produce the deficient labor climate in the performance of the workers, which they influence the labor performance of the own workers and of the municipal strengthening of Laredo's district the year 2012. The personalized individualized work takes form of the inadequate interpersonal relations, which they determine that the municipal organization contributes to the deficient cooperation and collective harmonic integration. The institutional identity related to the disinterest in the capture of conscience of the internal problematics that happens between the own workers and of his commitment, there affect in the deficient participation of activities for the contributions or offers of improvement organizacional that are realized in the Municipality distrital of Laredo.